(untitled) (Research, Society and Development, 2020)
This paper analyses political and pedagogical principles by Jean Jacques Rousseau (1712-1778), by identifying its contributions to the modern education of the child, the new school and liberalism. It is based on qualitative and bibliographical research guided by historical materialism. The text considers his works published in 1762, Emile or on Education and The Social Contract, whose contents address issues regarded the formation of man and citizen. The author prescribed a natural, negative education for the free child development, what is imperative for formation of the autonomous individual and his or her elevation to civilian life. When appreciating the child’s experience and activity, he attributes the function of making children’s lives their educational source to the educator, by inspiring existence pedagogy or new school. His educational propositions were associated to his liberal socio-political project that articulated the institution of a new democratic social contract to the citizen training. Rousseau has provoked questioning on child development, on didactic performance of teachers, and education necessary for the formation of man for life in society, what makes paramount the analysis of his contribution for the current education and society.